Financial Innovations And Financial Inclusion Among Commercial Banks in Uganda - Agaba, Agaba Moses; Mpirirwe Christine (International Journal of Entrepreneurship and Business Management, 2023)
This study was carried out to ascertain the impact of financial innovations by commercial banks on financial inclusion in the Kabale district. The specific goals were to ascertain the relationship between institutional innovations and financial inclusion, examine the relationship between process innovation and financial inclusion among rural households, and examine the relationship between product innovation and financial inclusion among rural households. The studies descriptive and cross-sectional research designs combined qualitative and quantitative methods for data collecting and analysis. Using questionnaires and interviews, data was gathered from a sample of 396 respondents as well as additional important informants. Microsoft EXCEL and SPSS Version 21.0 were used to analyze the data and produce both descriptive and inferential statistic . The study's findings support the statistically significant link between commercial banks' financial innovations and rural families' access to credit. As more clients choose mobile banking, the report advises banking institutions to develop measures to improve security in the platform. The report also advises making these platforms straightforward and simple to use in order to attract more users to the business. Additionally, because mobile banking has an impact on financial inclusion, banks should make sure to support mobile banking services by incorporating mobile phone usage as one of their innovations